2007
DOI: 10.1021/jf070946t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characterizations of Dehydroascorbate Reductase from Sesame (Sesamum indicumL.) Hairy Root Cultures

Abstract: Dehydroascorbate reductase (DHAR) is a biotechnologically or physiologically important reducing enzyme in the ascorbate-glutathione recycling reaction for most higher plants. A DHAR cDNA was isolated from sesame (Sesamum indicum L.) hairy roots, and its structure and biochemical properties were characterized to provide some information about its expressional and biochemical profiles in the hairy root cultures. The cDNA contained a catalytic motif CXXS, which may be indicative of a thiol-dependent redox functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The coloured potatoes had 1.7 to 2.5 times more the phenolics presumably due to the high anthocyanins in them and about 2 to 3 times more antioxidant capacity compared to unpigmented genotypes. These findings are in consistence with [5] [17] [26] and [27] who also reported greater amounts of bioactive compounds in coloured potatoes. No anthocyanins were detected in the unpigmented potatoes however; coloured genotypes had higher levels of anthocyanins.…”
Section: Potato Genotype Differences In Bioactive Compoundssupporting
confidence: 88%
See 1 more Smart Citation
“…The coloured potatoes had 1.7 to 2.5 times more the phenolics presumably due to the high anthocyanins in them and about 2 to 3 times more antioxidant capacity compared to unpigmented genotypes. These findings are in consistence with [5] [17] [26] and [27] who also reported greater amounts of bioactive compounds in coloured potatoes. No anthocyanins were detected in the unpigmented potatoes however; coloured genotypes had higher levels of anthocyanins.…”
Section: Potato Genotype Differences In Bioactive Compoundssupporting
confidence: 88%
“…One of the environmental signals that activate tuberization in potatoes is light. Delivery of light from the light-receiving organ, the leaf, to an underground organ growing in the dark, the stolon, leads to the formation of potato tuber [27] [36]. However, the underground tubers are exposed to darkness while the photosynthetically active leaf tissues are exposed to the light.…”
Section: Ascorbate Contents In Coloured Potatoesmentioning
confidence: 99%
“…Native PAGE showed that the molecular weight of the recombinant PbDHAR was less than 43 kDa (Figure 4C). These results strongly indicate that the recombinant PbDHAR is a monomer protein of 29.69 kDa, which is similar to other plant DHARs (Shimaoka et al 2000; Dixon et al 2002; Chun et al 2007).…”
Section: Resultssupporting
confidence: 60%
“…Further, structure-guided sequence alignment reveals a distinct positively charged pocket shared by these proteins [33] (Figure 1c, d). This pocket is occupied by conserved amino acids distributed around the catalytic CXX[C/S] motif [34]. In addition, the following residues; K8, F22, V60, P61, D73 and S74 which are part of the positively charged pockets of PgDHAR are also conserved in HsCLIC1 as well (K13, F26, L64, P65, D76 and T77) (Figure 1d).…”
Section: Resultsmentioning
confidence: 97%